The Monte Carlo method to build up models of the hydrolysis half-lives of organic compounds. Issue 6 (3rd June 2021) - Toropov, A.A.; Toropova, A.P.; Lombardo, A.; Roncaglioni, A.; Lavado, G.J.; Benfenati, E.
ABSTRACT: The hydrolysis of organic chemicals such as pesticides, pollutants, or drugs can affect the fate and behaviour of environmental contaminants, so it is of interest to evaluate the stability of substances in water for various purposes. For the registration of organic compounds in Europe, information on hydrolysis must be presented. However, the experimental measurements of all chemicals would require enormous resources, and computational models may become attractive. Applying the CORAL software (http://www.insilico.eu/coral ) quantitative structure-property relationships (QSPRs) were built up to model hydrolysis. The 2D-optimal descriptor is calculated with so-called correlation weights for attributes of simplified molecular input-line entry systems (SMILES). The correlation weights are obtained as results of the special Monte Carlo optimization. The nature of (five- and six-member) rings is an important component of this approach. Another important component is the atom pair proportions for nitrogen, oxygen, and sulphur. The statistical quality of the best model is: n = 44, r 2 = 0.74 (training set); n = 14, r 2 = 0.75 (calibration set); and n = 12, r 2 = 0.80 (validation set).